2019
DOI: 10.1103/physrevd.100.045017
|View full text |Cite
|
Sign up to set email alerts
|

Scattering amplitude recursion relations in Batalin-Vilkovisky–quantizable theories

Abstract: Tree-level scattering amplitudes in Yang-Mills theory satisfy a recursion relation due to Berends and Giele which yields e.g. the famous Parke-Taylor formula for MHV amplitudes. We show that the origin of this recursion relation becomes clear in the BV formalism, which encodes a field theory in an L 8 -algebra. The recursion relation is obtained in the transition to a smallest representative in the quasi-isomorphism class of that L 8 -algebra, known as a minimal model. In fact, the quasi-isomorphism contains a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 32 publications
1
94
0
Order By: Relevance
“…, x n ∈ L. With this definition, it can be shown that the minimal model theorem extends to cyclic L ∞ -algebras. For further details on this, see again the Appendix A of [10].…”
Section: )mentioning
confidence: 99%
See 4 more Smart Citations
“…, x n ∈ L. With this definition, it can be shown that the minimal model theorem extends to cyclic L ∞ -algebras. For further details on this, see again the Appendix A of [10].…”
Section: )mentioning
confidence: 99%
“…This theory should be thought of as a broad generalisation of Chern-Simons theory. In what follows, we shall only sketch the details and refer to [9] (see also [10]). Let L be an L ∞ -algebra with higher order brackets l n .…”
Section: Homotopy Maurer-cartan Theorymentioning
confidence: 99%
See 3 more Smart Citations